PROSPECTS FOR METROLOGY RELATED TO BIOLOGICAL RADIATION EFFECTS OF ION BEAMS. Issue 1 (17th December 2018) - Baek, Woon Yong; Dangendorf, Volker; Giesen, Ulrich; Hilgers, Gerhard; Nettelbeck, Heidi; Rabus, Hans
Abstract: In recent years, several approaches have been proposed to provide an understanding of the enhanced relative biological effectiveness of ion beams based on multi-scale models of their radiation effects. Among these, the BioQuaRT project was the only one which focused on developing metrology for a multi-scale characterization of particle track structure. The progress made within the BioQuaRT project has motivated the formation of a department 'Radiation Effects' at PTB dedicated to metrological research on ionizing radiation effects. This paper gives an overview of the department's present research directions and shortly discusses ideas for the future development of metrology related to biological effects of ion beams that are based on a stakeholder consultation.